The role and use of welfare technology in elderly care - Gil, Ana Paula (2020)
The paper presents facts and figures about Portuguese demography and its relation to the national institutional organisation of long-term care system. Hereby, the focus lies on “Digital Competence among long-term care system” where are presented elements of the current status of the use of technology and social innovations in elderly care institutions, specific policy initiatives and some “best practices” on the use of different technologies and innovations in Portugal. Second, the following chapters provides the “Implications for elderly, staff and working places” with regard to information technologies (IT) applied in the care work, or as mentioned in this report, to “welfare technologies”. There it is analysed the digital effects on organisation of work in long-term care system, the education problems and further training of care staff. The final chapters are about the challenges and risks of the use of technology in care work (covering the topics of integrity, ethical and economical challenges and risks), the societal debates, regulations and best practices, and, finally, the future perspectives and reflections.